Unsex CEDAW? No! Super-Sex It! - Hernandez-Truyol, Berta Esperanza (Columbia Journal of Gender and Law, 2011)
This Article reflects upon Darren Rosenblum’s provocative piece Unsex CEDAW or What s Wrong with Women’s Rights. At the outset I should note that this critical analysis should not be misinterpreted. I do not quarrel with Professor Rosenblum’s observations that inequality in law and life is much broader than sex inequalities. To the contrary, I am in full accord with him that discrimination along other categorical axes is also undesirable and sometimes as prevalent as sex inequality. Indeed, oftentimes such other discriminatory tendencies dovetail with those rooted in sex discrimination. Where we diverge, however, is in his proposal that the category woman, and the pursuit of equality rights utilizing a focus on sex, be eliminated altogether. He claims it is wrong to focus on women’s rights. Yet even in that regard I think our differences could be framed as methodological rather than substantive. Professor Rosenblum suggests that we unsex CEDAW and that the convention focus on gender in lieu of sex. Moreover, he posits that any consideration of discrimination on the basis of sex include men as well as women. I agree that the convention ought to protect against discrimination on the basis of gender as well as sex. Moreover, there is no question that the category sex includes men as well as women, although it is incontrovertible that the aim of CEDAW was to protect women because of the privations women experience in their lives-a reality around the world, north and south, east and west alike. Thus, our disagreement is narrow and centers on the ongoing relevance and significance- indeed, necessity-of the category woman.